Municipal Bonds and Monetary Policy: Evidence from the Fed Funds Futures Market. Issue 5 (15th February 2013) - Rosa, Carlo
Abstract This paper examines the impact of conventional and unconventional monetary policy on municipal bonds using a novel high‐frequency dataset. I use three proxies for monetary policy surprises: the surprise change to the current federal funds target rate, the surprise component in the Federal Open Market Committee (FOMC) balance‐of‐risk statement, and the unanticipated announcements of future large‐scale asset purchases. Estimation results show that monetary policy news have economically important and highly significant effects on municipal bond prices. Their daily responses are, however, substantially lower than the reaction of comparable Treasury notes. This work documents that market (in)efficiency, and the slow adjustment of municipal bond prices, can partially rationalize this discrepancy. © 2013 Wiley Periodicals, Inc. Jrl Fut Mark 34:434–450, 2014